Architecture of Class 1, 2, and 3 Integrons from Gram Negative Bacteria Recovered among Fruits and Vegetables - Jones-Dias, Daniela; Manageiro, Vera; Ferreira, Eugénia; Barreiro, Paula; Vieira, Luís; Moura, Inês B.; Caniça, Manuela (Frontiers in Microbiology, 2016)
The spread of antibiotic resistant bacteria throughout the food chain constitutes a public health concern. To understand the contribution of fresh produce in shaping antibiotic resistance bacteria and integron prevalence in the food chain, 333 antibiotic resistance Gram negative isolates were collected from organic and conventionally produced fruits (pears, apples and strawberries) and vegetables (lettuces, tomatoes and carrots). Although low levels of resistance have been detected, the bacterial genera identified in the assessed fresh produce are often described not only as environmental, but mostly as commensals and opportunistic pathogens. The genomic characterization of integron-harboring isolates revealed a high number of mobile genetic elements and clinically relevant antibiotic resistance genes, of which we highlight the presence of as mcr-1, qnrA1, blaGES-11, mphA and oqxAB. The study of class 1 (n=8), class 2 (n=3) and class 3 (n=1) integrons, harbored by species such as Morganella morganii, Escherichia coli, Klebsiella pneumoniae, led to the identification of different integron promoters (PcW, PcH1, PcS and PcWTNG-10) and cassette arrays (containing drfA, aadA, cmlA, estX, sat and blaGES). In fact, the diverse integron backbones were associated with transposable elements (e.g. Tn402, Tn7, ISCR1, Tn2*, IS26, IS1326 and IS3) that conferred greater mobility. This is also the first appearance of In1258, In1259 and In3-13, which should be monitored to prevent their establishment as successfully dispersed mobile resistance integrons. These results underscore the growing concern about the dissemination of acquired resistance genes by mobile elements in the food chain.